Literature Review: Hubungan Pertambahan Berat Badan Ibu Selama Kehamilan dengan Kejadian Berat Badan Lahir Rendah (BBLR) di Indonesia - Nurul Aini Wurdi Ningsih; Sri Sumarmi (Media Gizi Kesmas, 2023)
Background: Low Birth Weight (BBLR) is a case that occurs in baies after birth with indications of having a weight less than normal, which is less than 2500 grams. From Riskesdas data in 2018, stated that the incidence of LBW increased by 0,5% from 2013. Babies who has history of LBW have a chance of dying. Mother's weight during pregnancy is one of the risk factor of LBW, so mother who have weight gain in acoordance with the recommendations can prevent the incidence of LBW.                Objectives: The objectives of this literature review is to describe the relationship of gestational weight gain with Low Birth Weight (LBW) in Indonesia. Methods: Literature Review is a method that author uses to compose this articel. This research uses database from Google Scholar with related keyword and found 1.240 articles. Those articles had screened based on itopic and nclusion criteria, anda 9 articles were obtained that used for this literature review. Discussion: Six of nine journals stated that there was a relationship of gestational weight gain with Low Birth Weight (LBW), while three of other journal stated that gestational weight gain have not related with Low Birth Weight (LBW). The relationship of both variables is indicated by p-value is p < 0,05. Asniatin (2018), stated that risk factor of LBW is an abnormal mother weight gain, with 7,534 times greater chance of occurance. None of relationship of both variables is indicated by p value > 0,05. However, the result of research of Mamidi et al (2022), have a contradictive result research with Asniatin (2018). Conclusions: There are differences of opinion from several related studies. Prevention of LBW can be done early by monitoring health from pra conception until birth and paying attention to the factors of LBW.